2010
DOI: 10.1080/08941920903278137
|View full text |Cite
|
Sign up to set email alerts
|

Large Dams and Uncertainties: The Case of the Senegal River (West Africa)

Abstract: This paper examines the environmental and socio-economic consequences of hydraulic infrastructural changes along the Senegal River valley and estuary. During the 1980s, two dams were built along the valley floor to facilitate hydro-electrical production and regular water supply for crop irrigation. In 2003, a breach was dug across Barbary Spit to alleviate flooding in the nearby Saint-Louis city. Although these structures helped regulate the river flow, they also resulted in a series of unforeseen impacts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…For example, it has been shown that the construction of large dams has led to increases in human schistosomiasis in China, Cote d’Ivoire, Egypt, Ethiopia, Senegal [104], and Sudan, amongst others [105–107]. Dam spillways are known to serve as breeding sites for blackflies [108], and the construction of dams can lead to complex changes in habitat, which in addition to movement of non-immune populations and snails into the area can lead to transmission hotspots [109]. Evidence for beneficial inter-sectoral collaboration includes a study examining the impact of dam construction in Senegal and Mali, which showed the beneficial impact of control of water-related NTDs, including control of snails and mosquitoes [109].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that the construction of large dams has led to increases in human schistosomiasis in China, Cote d’Ivoire, Egypt, Ethiopia, Senegal [104], and Sudan, amongst others [105–107]. Dam spillways are known to serve as breeding sites for blackflies [108], and the construction of dams can lead to complex changes in habitat, which in addition to movement of non-immune populations and snails into the area can lead to transmission hotspots [109]. Evidence for beneficial inter-sectoral collaboration includes a study examining the impact of dam construction in Senegal and Mali, which showed the beneficial impact of control of water-related NTDs, including control of snails and mosquitoes [109].…”
Section: Main Textmentioning
confidence: 99%
“…Dam spillways are known to serve as breeding sites for blackflies [108], and the construction of dams can lead to complex changes in habitat, which in addition to movement of non-immune populations and snails into the area can lead to transmission hotspots [109]. Evidence for beneficial inter-sectoral collaboration includes a study examining the impact of dam construction in Senegal and Mali, which showed the beneficial impact of control of water-related NTDs, including control of snails and mosquitoes [109]. When initiating sustainable energy infrastructure, the existence of good control interventions for NTDs can ensure that the negative impact on health caused by NTDs will be mitigated.…”
Section: Main Textmentioning
confidence: 99%
“…This intrusion of seawater has increased salinization of land [9,10], surface water [11] and ground water [12]. Given the scale of this soil's degradation, several actions have been undertaken, including anti-salt dams [13,14]. So, the objective of this work was to understand the impact of these dams on the fluctuation of ground water during wet season.…”
Section: Introductionmentioning
confidence: 99%
“…The channel rapidly widened reaching 2.4 kilometers in 2006. As a result, the daily tidal range had a threefold increase (Mietton et al, 2007) and the estuary water salinity also increased, reducing the delta gardening, and threatening the remaining delta forest and pastures (Dumas et al, 2010).…”
Section: Changes In the Senegal River Estuarymentioning
confidence: 99%
“…The presence of dams and the associated hydraulic structures have contributed to the ecological and socio-economic changes in the Senegal River estuary as well (Dumas et al, 2010). In 2003, to protect Saint Louis town against periodic floods, a 4-m wide channel was dug across a narrow spit of sand that blocked the flow of the river to the ocean.…”
Section: Changes In the Senegal River Estuarymentioning
confidence: 99%